Performance analysis of machine learning classi ers for detecting PE malware - Azmee, ABM.Adnan; Choudhury, Pranto Protim; Alam, Md.Aosaful; Dutta, Orko (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.